Pre-service English Teachers Adaptation Skills in Two ESP Courses - Munir, Ahmad; Savitri, Wiwiet Eva; Asrori, Asrori; Chakim, Nur (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2023)
Background: The ability to adapt, imitate and modify knowledge in a learning context into another learning context is an important ability for students. However, the ability of pre-service English teachers to adapt their knowledge and skills from one course to other courses has not been studied. This research seeks to find out how pre-service English teachers in one state university in Indonesia adapt knowledge and skills acquired in the Syllabus Design (SD) and Developing EFL Materials (DEM) courses into ESP Program Design (ESP PD) and ESP Materials Development (ESP MD) courses. Methodology: This research is a mixed quantitative and qualitative study involving 54 students who have taken SD, DEM, ESP PD and ESP MD courses in 2022 in a state university in Indonesia. Fifteen of them also took part in a focus group discussion. Their answers to the semi-open questionnaire asking whether the 16 knowledge and skills learned in SD and DEM courses had been adapted were analyzed in a simple quantitative manner with percentages and modes. While the results of focus group discussion about how they adapted them were analyzed qualitatively for themes.Findings: The results of this study show that 15 knowledge and skills in SD and DEM courses were adapted by students into ESP PD and ESP MD courses. The participants adapted them by changing the context of the syllabus and materials the developed in SD and DEM from English at school to English for specific purposes in ESP PD and ESP MD especially when formulating learning objectives. They also developed general English materials into ESP English materials for certain occupations. These findings indicate that students master the contexts of ESP PD and ESP MD.Conclusion: It can be concluded that pre-service English teachers have excellent adaptation skills, which are done not by force, but by choice, to the peripheral component and for the benefit of students. Originality: This is the contribution of this research to students’ learning theory in ESP in English teacher education to add to Leko’s (2015) Evidence by Practice (EBP) theory.